Analisis Risiko Pembiayaan Murabahah pada Perbankan Syariah - Nasution, Syahdinar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
One of the important milestones in the development of the Islamic economy in Indonesia is the operation of Islamic banking. Sharia bank is one of the commercial banks that is developing in Indonesia that participates in providing support for economic development in Indonesia through financing efforts to customers and providing banking facilities and services to support people’s economic activities. One of the products/services in Islamic banking is murabahah. Customers generally use murabahah (sale and purchase) contracts to absorb financing, about 90% of murabahah is carried out at Islamic financial institutions. The high level of murabahah financing activities will certainly lead to high possible risks that will be faced by the financing provider entity. The research method used is normative juridical. This research was conducted on secondary data. To obtain data and research materials, data were obtained by conducting a literature review. The data collection technique is done through document study. The results of the study indicate that murabahah is one of the most dominant forms of financing in the current practice of Islamic banks. The provision of murabahah financing in the long term can pose risks. Specifically, the risks that occur in murabahah financing are related to goods that arise due to loss or damage from the time of purchase until the time of delivery. The strategies that must be carried out by Islamic banking in an effort to control the risk of murabahah financing include: the planning stage, the implementation stage and the control stage. In controlling the risk of murabahah financing, obstacles are often found. As for these obstacles, among others: financing constraints, supervision constraints and technological constraints.